IMPLEMENTASI DIGITAL SIGNATURE ALGORITHM (DSA) MENGGUNAKAN SECURE HASH ALGORITHM-256 (SHA-256) PADA MEDIA GAMBAR - Sahl Fawzy Sutopo, - (2020)
With the development of technology, documents not only produced in printed form but also produced in digital form, especially image documents. The advantage of digital documents is that they are easier and more efficient to use but digital documents are also easy to fake. To overcome this, a digital document security technique is needed, that is the document is digitally signed. This study aims to explain the process of implementing Digital Signature Algorithm by using the Secure Hash Algorithm-256 as hash function on image file and designing digital signature programs. The results of this study indicate that the Digital Signature Algorithm (DSA) using the Secure Hash Algorithm-256 hash function can't only be implemented in text messages, but can be implemented in image file by the method of image conversion to ASCII images. DSA can also be programmed using the Python programming language to facilitate the generation and authentication of signatures.